Oral Oncology Parity Laws, Medication Use, and Out-of-Pocket Spending for Patients With Blood Cancers. (27th December 2019) - Dusetzina, Stacie B; Huskamp, Haiden A; Jazowski, Shelley A; Winn, Aaron N; Wood, William A; Olszewski, Adam; Basch, Ethan; Keating, Nancy L
Abstract: Background: In this study, we sought to estimate the association between oral oncology parity law adoption and anticancer medication use for patients with chronic myeloid leukemia or multiple myeloma. Methods: This was an observational study of administrative claims from 2008 to 2017. Among individuals initiating tyrosine kinase inhibitors (TKIs) for chronic myeloid leukemia or immunomodulatory drugs for multiple myeloma, we compared out-of-pocket spending, adherence, and discontinuation before and after parity among individuals in fully insured plans (subject to parity) vs self-funded plans (exempt from parity) using propensity-score weighted difference-in-differences regression models. Results: Among patients initiating TKIs (N = 2082) or immunomodulatory drugs (N = 3326) there were no statistically significant differences in adherence or discontinuation associated with parity. The proportion of patients with initial out-of-pocket payments of 0 increased in fully insured plans after parity from 5.7% to 46.1% for TKIs and from 10.9% to 48.8% for immunomodulatory drugs. Relative to changes in self-funded plans, those in fully insured plans were 4.27 (95% CI = 2.20 to 8.27) times as likely to pay nothing for TKIs and 1.96 (95% CI = 1.40 to 2.73) times as likely to pay nothing for immunomodulatory drugs after parity. Similarly, the proportion paying more than 100 decreased from 30.3% to 24.7% for TKIs and 30.6% to 27.5% for immunomodulatory drugs in fully insured plans after parity. Relative to changes in self-funded plans, those in fully insured plans were 0.74 (95% CI = 0.54 to 1.01) times as likely to pay more than 100 for TKIs and 0.85 (95% CI = 0.68 to 1.06) times as likely to pay more than 100 for immunomodulatory drugs after parity. Conclusions: Among patients initiating TKIs or immunomodulatory drugs, parity was not associated with better adherence or less discontinuation of therapy but yielded decreased patient out-of-pocket payments for some patients.